Collaborative innovation, strategic agility, and absorptive capacity adoption in SMEs: The moderating effects of customer knowledge management capability - Mata, M. N.; Martins, J.; Inácio, P. (Journal of Knowledge Management, 2024)
Purpose The purpose of this study is to identify the relationship between collaborative innovation and the financial performance of information technology (IT) firms through the mediating role of strategic agility and absorptive capacity. Customer knowledge management capability (CKMC) is also explored as a potential moderator. Design/methodology/approach Data were collected from 300 respondents working in different small to medium IT enterprises operating in different cities around Portugal. The simple random sampling method was used for data collection, and Smart partial least squares-structural equation modeling (Smart PLS-SEM version 3.2.8) was used to test the hypotheses. Findings The findings demonstrate that collaborative innovation contributes significantly to the financial performance of IT firms in Portugal. The results also indicate that absorptive capacity and strategic agility both positively and significantly affect the relationship between collaborative innovation and firms’ financial performance. However, while the moderating role of CKMC has a positive and significant effect on the relation between collaborative innovation and strategic agility, CKMC insignificantly moderates the relation between collaborative innovation and absorptive capacity. Originality/value Few studies have explicitly connected collaborative innovation with firms’ financial performance; this study attempts to fill that gap. Moreover, this research investigates the mediating role of strategic agility and absorptive capacity in the relationship between collaborative innovation and financial performance. Finally, by discussing the moderating effect of CKMC, which leads to enhanced financial performance, this study proposes that when complex and unpredictable situations occur, managers should focus on customer-oriented strategies and innovation at the same time to outpace their competitors.